Penggunaan Alat Peraga Ular Tangga untuk Meningkatkan Hasil Belajar Siswa Mapel Geografi - Nurul Komari; Novita Sariani (Universitas Indraprasta PGRI Jakarta, 2019)
The lack of media to be a means of delivering material that has not been facilitated by schools is also a factor causing the low interest in student learning that has an impact on the student’s learning outcomes. The purpose of this study was to determine how the use of thematic snake ladder props in geography learning and improvement of student learning outcomes after using thematic snake ladder props in geography learning in class XI IPS Senior High Scholl 1 Sintang. The method used in this study is the action research method. The use of snake ladder thematic props in geography subjects in class XI Senior High School 1 of Sintang in cycle I had gone well and treatment in cycle II students understand more about the game rules so that students are more enthusiastic in learning by using thad thematic snakes and ladders in learning. . There was an increase in student learning outcomes in cycle I the percentage of students who were motivated towards learning by using the thematic snake ladder props were 72.72% of students who passed the test and in cycle II there were 81.81% and completeness Classical reached 81.81%.